Building a Profession from the Ground Up: A Longitudinal Study of Teacher Professional Development and Pedagogical Innovation in Papuan Private Schools - Iis Sugandhi; Arya Ganendra; Aaliyah El-Hussaini; Gayatri Putri; Evelyn Wang; Anita Havyasari; Muhammad Hasan (Enigma Institute, 2025)
Teacher quality is the most significant school-based determinant of student success, yet fostering professional excellence in remote and culturally diverse regions like Papua, Indonesia, presents profound challenges. Private schools often fill critical educational gaps but their teachers can be professionally isolated. This study addressed the gap in long-term, evidence-based research on teacher professional development (TPD) in this unique context. A three-year (2021-2024) concurrent mixed-methods longitudinal study was conducted. The study involved 50 teachers from a network of five private schools in urban, semi-rural, and remote highland regions of Papua. A comprehensive TPD program, focusing on student-centered learning and culturally responsive pedagogy, was implemented. Quantitative data were collected annually using the Teacher Pedagogical Knowledge Test (TPKT), the Teacher Self-Efficacy Scale (TSES), and a structured Classroom Observation Protocol. Qualitative data were gathered through semi-structured interviews, teacher reflective journals, and focus group discussions with Professional Learning Communities (PLCs). Quantitative data were analyzed using repeated measures ANOVA, while qualitative data were analyzed thematically. The longitudinal quantitative analysis revealed statistically significant improvements across all three years. Mean TPKT scores increased from 48.5 (SD=11.2) at baseline to 79.8 (SD=8.5) at endline (F(2, 98) = 157.2, p <0.001). Teacher self-efficacy scores also showed significant growth (F(2, 98) = 112.9, p <0.001). Classroom observations confirmed a marked shift from teacher-centered to student-centered practices. Qualitative findings identified three core themes: (1)